Guide to the psychiatry of old age - Ames, David, 1954- 4 0 16; Dr. Gallagher, Damien,;Loi, Samantha,;Russ, Tom; 5 (Cambridge, United Kingdom ;;New York, NY : Cambridge University Press, 2022)
Emeritus Professor of Psychiatry, University of Melbourne Academic Unit for Psychiatry of Old Age and National Ageing Research Institute, Parkville and consultant psychiatrist for Royal Melbourne, St George's and Epworth Camberwell Hospitals, all in Melbourne. David Ames is an experienced old age psychiatrist who has worked both clinically and academically in the field for 31 years. He has edited/written over 20 books, over 250 peer reviewed research papers and led the first edition of this book. is an old age psychiatrist in Sunnybrook Health Sciences Centre, Toronto, Canada and assistant professor with the University of Toronto. His clinical and research interests include the neurobiology of depression in later life and associated cognitive dysfunction. In his work he has explored modifiable risk factors for cognitive decline and is now engaged in interventional studies to improve treatment outcomes for older adults with behavioural and neurocognitive disorders in later life. Samantha Loi is an old age psychiatrist working at the Royal Melbourne Hospital, Australia in the Neuropsychiatry Unit since 2015. She is also a senior lecturer at the University of Melbourne Academic Unit for Psychiatry of Old Age and recently received her PhD qualification. She has extensive clinical experience and her research interests include carer well-being and the use of modern technology to improve quality of life of older adults. Intermediate Clinical Fellow at the Centre for Dementia Prevention and Alzheimer Scotland Dementia Research Centre, both at the University of Edinburgh, and an Honorary Consultant Psychiatrist for NHS Lothian--
What is the psychiatry of old age and why do we need it? -- Assessment of the elderly psychiatric patient -- Differential diagnosis - the 3 Ds -- The dementias -- Behavioural and psychological symptoms of dementia -- Delirium -- Mood disorders in late life -- Schizophrenia and related disorders in late life -- Neurotic and personality disorders -- Substance abuse and iatrogenesis in late life -- Services for older patients with psychiatric disorders -- The future of the psychiatry of old age.
Preceded by Guide to the psychiatry of old age / David Ames ... [et al.]. 2010.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: 2 -- 0; 6; methods -- Mental Disorders;Aged;Geriatric Psychiatry -- 20; 20; 2